Peran Kasepuhan Sebagai Modal Sosial Trust Dalam Tradisi Pantang Mulud Di Desa Pamubulan - Sidqiyah, Chamiyatus; Khoiriyah, Nunung; Fitriyani, Ainun Intan; Safitri, Alfiaturrochmah; Nisa, Syakilatun; Ivena, Najela Naqiyya; Al-Fathan, Ahmad Fajri (LPPM Universitas Dharma Andalas, 2025)
The Pantang Mulud tradition within the Kasepuhan community of Pamubulan Village, Lebak Regency, Banten, constitutes a significant social phenomenon that actively builds trust-based social capital. This qualitative case study research specifically investigates the relationship between religious traditions and the strengthening of social capital, with particular emphasis on the trust dimension. Data collection was conducted through intensive participatory observation, comprehensive in-depth interviews with key informants (including Olot, community leaders, and active residents), and systematic documentation studies. The data analysis strategically integrated the SOCAT Instrument developed by Grootaert & Van Bastelaer (2002) with Robert Linton’s foundational Role Theory (1936). The research results clearly demonstrate that through various traditional activities – including Tuesday prohibitions, customary deliberations, the kepret ritual, and the Tang-Tang Angin procession – this tradition effectively constructs four distinct forms of trust: (1) trust in the system through voluntary compliance with customary norms, (2) trust in authority through demonstrated confidence in Kasepuhan’s leadership, (3) interpersonal trust within traditional social networks, and (4) transformative trust through collective action in the “Nganjingan” program. The study findings further reveal that trust within the Kasepuhan community fundamentally stems from the Kasepuhan’s consistent role performance in fulfilling community expectations. Ultimately, the Kasepuhan institution serves as a crucial catalyst that significantly strengthens solidarity, cultural identity, and social participation while simultaneously mobilizing social capital for sustainable community welfare.